Development of the measure of assessment self-efficacy (MASE) for quizzes and exams. Issue 6 (2nd November 2022) - Riegel, Kaitlin; Evans, Tanya; Stephens, Jason M.
ABSTRACT: Self-efficacy is a significant construct in education due to its predictive relationship with achievement. Existing measures of assessment-related self-efficacy concentrate on students' beliefs about content-specific tasks but omit beliefs around assessment-taking. This research aimed to develop and test the Measure of Assessment Self-Efficacy (MASE), designed to assess two types of efficacy beliefs related to assessment (i.e. 'comprehension and execution' and 'emotional regulation') in two scenarios (i.e. a low-stakes online quiz and a high-stakes final exam). Results from confirmatory factor analysis in Study 1 ( N  = 301) supported the hypothesised two-factor measurement models for both assessment scenarios. In Study 2, results from MGCFA ( N  = 277) confirmed these models were invariant over time and provided evidence for the scales' validity. Study 3 demonstrated the exam-related MASE was invariant across cohorts of students ( N s = 277; 329). Potential uses of the developed scales in educational research are discussed.